Pengaruh Penambahan Asam Amino Triptofan Pada Pakan Buatan Terhadap Kelangsungan Hidup dan Pertumbuhan Ikan Kapiat (Barbonymus schwanenfeldii) - Al Rasyid, Muhammad Fauzan; Isriansyah, Isriansyah; Ma’ruf, Mohamad (Jurnal Akuakultur Sungai dan Danau, 2026)
This study aims to analyze the effect of artificial feed with different doses of tryptophan amino acid supplementation and determine the appropriate dose of tryptophan amino acid supplementation on the survival and growth rate of tinfoil barb (B. schwanenfeldii). This study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications : P1 (0% tryptophan), P2 (1% tryptophan), P3 (2% tryptophan), and P4 (3% tryptophan). The results showed that the supplementation of tryptophan amino acid to artificial feed did not significantly affect survival and growth, as well as feed utilization efficiency and feed conversion ratio. The supplementation of tryptophan amino acid to artificial feed resulted in 100% survival rate in all treatments. The highest growth rate in total length was achieved in treatment P2 (1%), the highest growth rate in absolute weight was achieved in treatment P2 (1%), and the highest growth rate was achieved in treatment P2 (1%). the highest result for feed efficiency was obtained in treatment P2 (1%), and the lowest result for food conversion rasio was obtained in treatment P2 (1%). The lowest results for total length growth, absolute weight growth, growth rate, and feed efficiency were obtained in treatment P4 (3%), while the highest food conversion rasio was obtained in treatment P4 (3%). Water quality parameters during the rearing period were still considered suitable to support the survival and growth of tinfoil fish (B. schwanenfeldii).